Evaluation of decellularized human umbilical vein (HUV) for vascular tissue engineering – comparison with endothelium‐denuded HUV. (5th October 2012) - Mangold, Silvia; Schrammel, Siegfried; Huber, Georgine; Niemeyer, Markus; Schmid, Christof; Stangassinger, Manfred; Hoenicka, Markus
Abstract Human umbilical vessels have been recognized as a valuable and widely available resource for vascular tissue engineering. Whereas endothelium‐denuded human umbilical veins (HUVs) have been successfully seeded with a patient‐derived neoendothelium, decellularized vessels may have additional advantages, due to their lower antigenicity. The present study investigated the effects of three different decellularization procedures on the histological, mechanical and seeding properties of HUVs. Vessels were decellularized by detergent treatment (Triton X‐100, sodium deoxycholate, IGEPAL‐CA630), osmotic lysis (3 m NaCl, distilled water) and peroxyacetic acid treatment. In all cases, nuclease treatments were required to remove residual nucleic acids. Decellularization resulted in a partial loss of fibronectin and laminin staining in the subendothelial layer and affected the appearance of elastic fibres. In addition to removing residual nucleic acids, nuclease treatment weakened all stainings and substantially altered surface properties, as seen in scanning electron micrographs, indicating additional non‐specific effects. Detergent treatment and osmotic lysis caused failure stresses to decrease significantly. Although conditioned medium prepared from decellularized HUV did not severely affect endothelial cell growth, cells seeded on decellularized HUV did not remain viable. This may be attributed to the partial removal of essential extracellular matrix components as well as to changes of surface properties. Therefore, decellularized HUVs appear to require additional modifications in order to support successful cell seeding. Replacing the vessels' endothelium may thus be a superior alternative to decellularization when creating tissue‐engineered blood vessels with non‐immunogenic luminal interfaces. Copyright © 2012 John Wiley & Sons, Ltd.